Pengembangan Model Sistem Informasi Manajemen Administrasi Sekolah Berbasis Website “SIMANIS SISTE” untuk Meningkatkan Layanan Sekolah YPK di Kabupaten Jayapura - Wally, Maikel; Satyawati, Sophia (Kelola: Jurnal Manajemen Pendidikan, 2025)
This research aims to develop a school management information system model named "SIMANIS SISTE," a web-based platform designed to improve the administrative services of YPK schools in Jayapura Regency. This study addresses the need for a more effective and efficient administrative system to support educational services. The research employed the ADDIE development model, comprising five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, and validations by school administration and information technology experts. A limited trial was conducted, involving the principal as the admin, two teachers as editors, and seven teachers as authors. Research instruments included closed and open-ended questionnaires and observation sheets. The findings indicate that the "SIMANIS SISTE" model achieved a very high validity score, with an average of 91%, making it suitable for implementation. The system has proven effective in enhancing school administrative efficiency, featuring tools that facilitate data management, user collaboration, and information accessibility. Additionally, user suggestions regarding interface optimization and usage guidelines were incorporated into system improvements. These findings demonstrate that implementing "SIMANIS SISTE" can serve as an innovative solution to address school administration challenges and enhance the quality of educational services in YPK schools in Jayapura Regency.